THE ISSUE OF JUDICIAL COMPETENCE IN THE SETTLEMENT OF SHARIA ECONOMIC INSOLVENCY - Dwi Seno Wijanarko (Awang Long Law Review, 2021)
Settlement of bankruptcy disputes, according to Sharia banking law. Based on UUPA No:3 of 2006 related to the authority of the Religious Court to examine sharia economic disputes and based on PERMA No: 2 of 2008 on the Compilation of Sharia Economic Law decided directly by the Supreme Court referring to Law No: 27 of 2004 which appoints about the Commercial Court. Whereas the Religious Court that has the authority of bankruptcy disputes contains elements of Sharia Economics, including Islamic banking. Insolvency Decision No: 7/ Bankruptcy/2011/PU. Niaga JKT PST strengthened MARI Verdict No: 346F/PDT. SUS / Year 2011 which does not consider the existence of PERMA Number: 2 of 2008 on Compilation of Economic Law established by the Supreme Court.